(untitled) (Journal of International Crisis and Risk Communication Research, 2021)
This qualitative study analyzes the Greek government’s crisis management practice and public communication efforts during two waves of the COVID-19 pandemic in 2020. Integrating both crisis management theories and the World Health Organization’s pandemic control plans, discourse analysis and case study approaches were taken to analyze how Greek’s key government and public health authorities communicated with the public using different frames and crisis response strategies. Evaluations were conducted to assess the Greek government’s crisis communication procedures and the effectiveness of different rhetorical strategies used as evidenced in public briefings and public speeches.